Druggability Evaluation of the Neuron Derived Orphan Receptor (NOR‐1) Reveals Inverse NOR‐1 Agonists. (7th July 2022) - Zaienne, Daniel; Arifi, Silvia; Marschner, Julian A.; Heering, Jan; Merk, Daniel
Abstract: The neuron derived orphan receptor (NOR‐1, NR4A3) is among the least studied nuclear receptors. Its physiological role and therapeutic potential remain widely elusive which is in part due to the lack of chemical tools that can directly modulate NOR‐1 activity. To probe the possibility of pharmacological NOR‐1 modulation, we have tested a drug fragment library for NOR‐1 activation and repression. Despite low hit‐rate (<1 %), we have obtained three NOR‐1 ligand chemotypes one of which could be rapidly expanded to an analogue comprising low micromolar inverse NOR‐1 agonist potency and altering NOR‐1 regulated gene expression in a cellular setting. It confirms druggability of the transcription factor and may serve as an early tool to assess the role and potential of NOR‐1. Abstract : Drug fragment screening and subsequent SAR evaluation identified an inverse agonist of the neuron derived orphan receptor (NOR‐1) for which chemical tools are rare. The inverse agonist blocked the interaction of NOR‐1 with the co‐regulator SMRT and enhanced expression of the c‐MYC proto‐oncogene (MYC) which is directly suppressed by NOR‐1 thus confirming inverse NOR‐1 agonism in cellular setting.